2022
DOI: 10.3389/fenvc.2022.890408
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of graphene and graphene-based nanocomposites: Conventional to artificial intelligence approaches

Abstract: Recent advances in graphene research have enabled the utilization of its nanocomposites for numerous energy-based and environmental applications. Recently, the advancement in graphene-based polymer nanocomposites has received much attention with special emphasis on synthesis and application. Graphene-based nanocomposites show astonishing electrical, mechanical, chemical, and thermal characteristics. Graphene nanocomposites (GNCs) are synthesized using a variety of methods, including covalent and non-covalent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 258 publications
0
4
0
Order By: Relevance
“…Carbon forms many allotropes, with the major ones being graphite and diamond. Graphene is extracted from graphite using a technique called micromechanical cleavage [25]. GBNs are synthesized through diverse methods, encompassing covalent and non-covalent approaches, chemical deposition, hydrothermal growth, electrophoresis deposition, and physical deposition [26].…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…Carbon forms many allotropes, with the major ones being graphite and diamond. Graphene is extracted from graphite using a technique called micromechanical cleavage [25]. GBNs are synthesized through diverse methods, encompassing covalent and non-covalent approaches, chemical deposition, hydrothermal growth, electrophoresis deposition, and physical deposition [26].…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…Consequently, future investigations should focus on harnessing AI technology to enable the development of comprehensive databases and facilitate more accurate predictions of material characteristics in photocatalysis. By leveraging AI techniques, researchers can surmount the challenges posed by the diverse and voluminous datasets associated with various photocatalyst designs [293][294][295]. Machine learning algorithms can be employed to analyze and integrate this data, uncovering meaningful patterns and relationships that would be otherwise difficult to discern.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Its physicochemical properties include strong electrical and thermal conductivities, a large surface area, carrier mobility, chemical stability, optical transmittance, and mechanical strength . Due to these excellent properties, graphene has been applied in potential fields, such as optoelectronics, photonics, energy, industry, and environmental remediation . However, the poor solubility of graphene in biological media is one of the obstacles to its application in biomedical applications. , To solve this obstacle, graphene oxide (GO) and reduced graphene oxide (rGO) have been successfully applied in biomedicine and environmental applications due to their oxygenated functional group. , For example, Mittal et al reported that both GO/rGO exhibited high anticancer activity in A549 cells.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Due to these excellent properties, graphene has been applied in potential fields, such as optoelectronics, photonics, energy, industry, and environmental remediation. 3 However, the poor solubility of graphene in biological media is one of the obstacles to its application in biomedical applications. 4 , 5 To solve this obstacle, graphene oxide (GO) and reduced graphene oxide (rGO) have been successfully applied in biomedicine and environmental applications due to their oxygenated functional group.…”
Section: Introductionmentioning
confidence: 99%